Role of umbilical artery Doppler velocimetry in predicting the adverse perinatal outcomes in hypertensive disorder of pregnancy - Yadav, Jyoti; Shukla, Mala; Jain, P. K.; Kumar, Devender (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Early detection of fetoplacental compromise with Umbilical Artery Doppler indices and to know the predictive value of each indices in predicting perinatal outcome and interventional strategies in these patients. Methods: The present prospective study was conducted on 200 women with hypertensive disorder of pregnancy. Umbilical artery doppler evaluation done in all the patients at (28-32) weeks, (33-36) weeks and (37-40) weeks of gestation and more frequently in those patients having deranged Doppler. Patients divided into two groups women with abnormal Umbilical artery indices (group B) and normal indices (group A). Perinatal outcome of both the groups were compared, analyzed statistically using Chi-square test. Multiple pregnancy, chronic hypertension, fetal congenital anomalies, systemic disease and those lost to follow up till delivery were excluded from study. Results: A total of 200 pregnant women with hypertensive disorder, 64% were primgravida. Abnormal umbilical artery indices seen in 36%. Adverse outcome was seen in 88.88% patients of group B. Statistically significantly higher rate of caeserian section, induction of labour, Preterm delivery, fetal growth restriction, NICU admission, NICU stay >48hrs were seen in group B. In all indices Umbilical artery PI had highest Sensitivity (84.21%), positive predictive value (88.88%) and accuracy (90%). Conclusions: Umbilical artery PI is the most reliable to predict adverse perinatal outcomes and help in appropriate timing of intervention to improve perinatal outcome.